Uporaba nevronskih mrež pri iskanju parov Higgsovih bozonov - Tomšič, Andraž (Matrika, 2023)
Experimental confirmation of the formation of Higgs boson pairs is crucial in confirming the theory of the Standard Model or checking hypotheses outside of this theory. This article presents the physical basis of the formation, decay and detection of such pairs. Additionaly it introduces the application of neural networks in the separation of detected particles created from a pair of Higgs bosons and detected particles created from other processes.
Keywords: fizika osnovnih delcev; Higgs bosons; Higgsovi bozoni; machine learning; neural networks; nevronske mreže; physics of elementary particles; strojno učenje